Synthesis, characterization, and performance evaluation of Al2O3 nanoparticles in HFE7000 refrigerant for domestic refrigeration - Digra, Munish; Singh, Jagdev (Frontiers in Thermal Engineering, 2025)
Nanorefrigerants, which consist of base refrigerant enhanced with nanoscale particles, represent a promising advancement in thermal management systems. This study reports the successful synthesis, characterization, and experimental evaluation of a novel Al2O3/HFE-7000 nanorefrigerant intended for domestic refrigeration applications. Aluminum oxide (Al2O3) nanoparticles were synthesised via a citrate sol-gel method, followed by calcination at 800 °C, and characterised using Powder X-ray Diffraction (PXRD), Field Emission Scanning (FESEM), High Resolution Transmission Electron Microscopy (HRTEM), Energy-Dispersive X-ray Spectroscopy (EDX), and Brunauer-Emmett-Teller (BET) analyses. The nanoparticles exhibited high crystallinity, spherical morphology, an average size of ∼22.5 nm, and a surface area of 26.2 m2/g with mesoporous structure. The nanorefrigerant was prepared by dispersing Al2O3 nanoparticles in HFE-7000 using ultra sonication and magnetic stirring, aided by Tween-80 surfactant to ensure long-term dispersion stability. Five different nanoparticle concentrations (0.02%–1.5% wt) were tested. A custom-engineered vapour compression refrigeration system (VCRS) test rig was deployed to evaluate the thermophysical performance across five temperature conditions. Key findings revealed that the addition of Al2O3 significantly enhanced the Coefficient of Performance (COP), improved subcooling, and reduced the discharge pressure and compression ratio—without compromising system stability. The optimal concentration range was identified as 1.2–1.4 wt%, beyond which increases in viscosity and potential nanoparticle agglomeration could offset thermal benefits. These results highlight the potential of Al2O3/HFE-7000 nanorefrigerants as high-efficiency, environmentally friendly alternatives for domestic cooling applications.